(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
In Ethiopia, traditional beekeeping systems with low productivity and quality predominate in the beekeeping industry, which contributes only less than 1.3% of Ethiopia’s agricultural GDP. Despite government extension services, farmers resist adapting to the improved technology due to high prices and accessibility. Hence, this study was conducted to estimate the amount of economic loss due to the use of traditional technology using 165 randomly selected beekeepers in three purposefully selected zones in the Oromia regional state in Ethiopia. The study found that about 83% of the respondents have been relying on traditional beehives for both honey and colony survival. However, the traditional beehive production system is associated with lower productivity, lower quality, higher post-harvest losses, and lower income rewards. In practice, most MFH[1] and KTB[2] hives are managed nearby homes, whereas 63% of traditional hives are fixed on trees in the forest or nearby homes. This causes the beekeepers to harvest only once from traditional beehives, which also contributes to colony loss and a lower honey harvest. With this practice, the beekeepers in regions, in general, lose about 15 billion ETB[3] annually due to lower productivity of the technologies, traditional beehives, and colony losses. Thus, the region can recover these losses through better management and less reliance on conventional beehives. Vol. 10, No. 3, December 2023: 285-292